Role of Certain Plant Ingredients on Hair Disorders. - Bhutia, Subrat Kumar; Das, Arun Kumar (International Research Journal of Ayurveda & Yoga, 2023)
For maintaining healthy, attractive appearance hair has the vital role. Hair problems are common and can diminish self-esteem and self confidence of a person. Many forms of hair problems, baldness, alopecia, hair fall, gray hair, dryness, and most common dandruff require clinical care by a health care professional. Hair is sensitive to changes in the environment, diet, and overall health. Identifying these changes and resorting to the wisdom of Ayurveda for their coping mechanisms can help maintain good hair health. Ayurveda formulations always have attracted considerable attention because of their good activity and comparatively lesser side effects with synthetic drugs. This review gives knowledge regarding the beneficial effects and recent progress of medicinal plants for the treatment of hair disorders.